2019
DOI: 10.1038/s41467-018-07770-1
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA analysis identifies cellular heterogeneity and adaptive responses of the lung at birth

Abstract: The respiratory system undergoes a diversity of structural, biochemical, and functional changes necessary for adaptation to air breathing at birth. To identify the heterogeneity of pulmonary cell types and dynamic changes in gene expression mediating adaptation to respiration, here we perform single cell RNA analyses of mouse lung on postnatal day 1. Using an iterative cell type identification strategy we unbiasedly identify the heterogeneity of murine pulmonary cell types. We identify distinct populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
212
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(234 citation statements)
references
References 71 publications
22
212
0
Order By: Relevance
“…TFs assigned to the first major fate split are known regulators for lung epithelial fate including the distal lung developmental regulator SOX9 (Perl et al, 2005;Rockich et al, 2013) and HMGA2, a TF highly expressed in human distal lung bud tip cells (Nikolic et al, 2017) and lung epithelial carcinomas (Snyder et al, 2013). For the lower lung epithelial path to iAEC2 fate (P3-P6, black arrow) the model identified ATF4, CEBPδ and ZNF503 as top TFs most associated with iAEC2 fate, findings in keeping with recent analyses of new-born lungs where CEBPδ and ATF4 are TFs highly expressed in the alveolar epithelium in vivo at post-natal day 1 (Guo et al, 2019). We validated performed siRNA-based knockdown of CEBPδ in iPSC-derived iAEC2s and found this resulted in reduced SFTPC, SFTPB, ABCA3, and SFTPA1 gene expression levels without altering endodermal (FOXA2) or lung TF (NKX2-1) levels ( Figure 4F Figure 4G).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…TFs assigned to the first major fate split are known regulators for lung epithelial fate including the distal lung developmental regulator SOX9 (Perl et al, 2005;Rockich et al, 2013) and HMGA2, a TF highly expressed in human distal lung bud tip cells (Nikolic et al, 2017) and lung epithelial carcinomas (Snyder et al, 2013). For the lower lung epithelial path to iAEC2 fate (P3-P6, black arrow) the model identified ATF4, CEBPδ and ZNF503 as top TFs most associated with iAEC2 fate, findings in keeping with recent analyses of new-born lungs where CEBPδ and ATF4 are TFs highly expressed in the alveolar epithelium in vivo at post-natal day 1 (Guo et al, 2019). We validated performed siRNA-based knockdown of CEBPδ in iPSC-derived iAEC2s and found this resulted in reduced SFTPC, SFTPB, ABCA3, and SFTPA1 gene expression levels without altering endodermal (FOXA2) or lung TF (NKX2-1) levels ( Figure 4F Figure 4G).…”
supporting
confidence: 81%
“…Based on prior literature (Frank et al, 2016;Hogan et al, 2014;Jacob et al, 2017), and significant differential expression between primary fetal and adult AEC2s, we also selected downregulation of Wnt targets LEF1 and BAMBI and the transcription factor SOX9 as additional stage-dependent maturation markers of AEC2s, although SOX9 variance was not in the top 1000 varying genes overall. Taken together our profiles indicate the early development of distal human lung epithelium is characterized by the expression of a subset of surfactant-and lamellar body-associated genes, some of which increase non-linearly over time (Figure 1C and D), followed by later expression of genes associated with AEC2 maturation, including expression of the full complement of surfactant proteins and additional markers that others have observed in adult AEC2s Treutlein et al, 2014) (Guo et al, 2019). Conversely, maturation of AEC2s is associated with decreasing Wnt signalling consistent with prior findings in vivo in mice (Frank et al, 2016) as well is in vitro in AEC2s (iAEC2) .…”
Section: Transcriptomic Profiles Of Primary Human Developing Lung Alvsupporting
confidence: 69%
“…We further evaluated CoBATCH data on the tissue-enriched enhancer regions by inspection of aggregate single cells across tissues. Evidently, robust H3K27ac enrichment was produced around the enhancer regions of TFs reflecting tissue developmental origins, Foxf2 for brain 18 , Gata4 for heart 19 , Hoxa11 for kidney 20 , Foxf1 for lung 21 and Cdx2 for small intestine 22 (Figure 3C). Hierarchical clustering of aggregate single cells showed that limb muscle, skin and small intestine were significantly separated from other tissues.…”
mentioning
confidence: 94%
“…The sources of this marker gene list included information from the Mouse Cell Atlas, ToppGene, and Lung Gene Expression Analysis (LGEA) (75)(76)(77). Additionally, we manually collected cell marker genes from published scRNA-seq studies performed in mouse or human lung (73,78). One-tailed Fisher exact test was used to perform enrichment analysis between marker genes for each cluster and the curated reference markers of known lung cell types.…”
Section: Animalsmentioning
confidence: 99%
“…On the last day of exposure, the mice were sacrificed, lung harvested, and tissue immediately placed in ice-cold PBS. Dissociation of the pooled whole mouse lung for each group (IH vs RA) was performed as previously described(73). Briefly, minced lung was placed in collagenase/elastase/dispase digestion buffer (Sigma-Aldrick, St. Louis, MO; Worthington Biochemical, Lakewood, NJ).…”
mentioning
confidence: 99%